2003
DOI: 10.1016/s0045-6535(02)00319-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of biofilm extracellular polymeric substances

Abstract: This study discovered that biofilm extracellular polymeric substances (EPS) are biodegradable by their own producers and by other microorganisms when they are starved. The study was performed in a comparative fashion to examine the biodegradability of biofilm EPS by the microorganisms from the original biofilm (its own producers) and from activated sludge (other microorganisms). Four distinctive phases were observed during EPS biodegradation. In the first phase, instantaneous concentration increases of carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(119 citation statements)
references
References 11 publications
(8 reference statements)
5
109
0
5
Order By: Relevance
“…However, after the 12 cm point, the protein content became relatively constant or decreased slightly over time. Similarly to the LP results, this might be related to substrate depletion in the most biologically active zone of the column (up to 12 cm), with remaining viable cells utilizing mainly the EPS under these starvation conditions (Zhang and Bishop, 2003).…”
Section: Structural Composition Of Biofilmsupporting
confidence: 59%
“…However, after the 12 cm point, the protein content became relatively constant or decreased slightly over time. Similarly to the LP results, this might be related to substrate depletion in the most biologically active zone of the column (up to 12 cm), with remaining viable cells utilizing mainly the EPS under these starvation conditions (Zhang and Bishop, 2003).…”
Section: Structural Composition Of Biofilmsupporting
confidence: 59%
“…Once the Roseobacter clade bacterial climax population is reached, some of the cells may leave the surface to avoid overcrowding, or they may become less active due to limited availability of nutrients and other resources or to aging and death of the bacterial cells because of phage infection, protozoan grazing, or other microbial interactions (23,42,52,54). The accumulation of EPS and other biopolymers may make the surface physicochemical properties significantly different from those of the initial conditioning film-covered surface, thus allowing other microbes to grow or colonize (63). One of the options may be the Bacteroidetes bacteria, which are active biopolymer utilizers and are abundant in natural aquatic biofilms and particles (25,41,60).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria convert the initial surface-accumulated nutrients and energy (whose levels may be very low in nature) into biomass and extracellular products, which may be exploited by the latestage microbes for nutrients or microhabitats (63). As the keystone primary colonizers, the Roseobacter bacteria provide the important transition of the submerged surfaces from lownutrient status (covered with conditioning film) to high-nutrient status (covered with abundant EPS and other biopolymers) for the succession and maturation of the surface-colonizing microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…S91 for growth and detachment, but our experiments were not designed to detect this. Zhang & Bishop (2003) found that some biofilmassociated microorganisms were capable of degrading extracellular polymeric substances, produced during biofilm formation, when under conditions of starvation. Additionally, in mixed-species consortia, a species not responsible for extracellular polymeric substance production was seen to benefit from its consumption (Zhang & Bishop 2003).…”
Section: Discussionmentioning
confidence: 99%